Cultivo de Lentinus sajor-caju (Fr.) Fr. [=Pleurotus sajor-caju (Fr.) Singer] e Pleurotus spp. em diferentes substratos - Albuquerque, Margeli Pereira de (2010)
The Pleurotus species, popularly known as oyster mushroom, are primary decompositers of woods and others biodegradables wastes. These mushrooms show nutricional proprieties with higher proteins, essencial aminoacids, unsaturated fat acids, vitamins and mineral contents, however are becoming as an important food resource. The substrata identification are the mainly stage in the productivity increase studies in the fungiculture. The in vitro and in vivo cultures aim to elucidate the optimal conditions of fungi growing related to a culture media that allow the fast development and increase the productivity. For Pleurotus spp. the currently strains available, were selected by the use of different ways of culture, aimed to increase the productivity. Therefore, these works aim to study the in vitro micelial growth and colonization of substratum and the productivity of three mushrooms strains in different agricultural wastes. Three experiments were carried out to reach the objectives, using rice straw, castor bean seed husks and peanut shells as substrata. In the first experiment, the strains was repicated to a petri dishes, with a solid medium prepared with the selected substrata, and incubated at 25°C. The mycelial growing was daily mensured with ruler and at the end of experiment the mycelial biomass was quantified. In the second experiment was evaluated the colonization capacity under in vitro conditions. The strains were repicated to the tubes with pasteurized susbtrata and incubated at 28°C. Were measured, in intervals of 24 hours, the distance of mycelia from the colonization origin for each tube. In the third experiment were evaluated the productivity, biological efficiency, the fresh and dry mass and the centesimal composition of the basidiomata produced in the selected substrata, beyond the carbon/nitrogen ratio in each substrata before and after the 66 days of cultive. The medium formulated with peanut shells extract propritiated the higher vegetative growing of Lentinus sajor-caju (PSC01/06) mycelia. The strain POR01/06 of Pleurotus ostreatoroseus, demonstrate the higher mycelial growing in the castor bean seed husks extract medium. The wild strain of Pleurotus pulmonarius grows indifferently in both tested media, moreover shows the highest mycelial growing that P. ostreatoroseus. The results of second experiment concludes that the rice straw provides faster colonization of Lentinus sajor-caju when it compares with the others substrata. The castor bean seed husks and the peanut shells substrata provides a slowly linear colonization for P. ostreatoroseus. The results of the third experiment allow to conclude that Lentinus sajor-caju as revealed such the most promising for the fungiculture, showing 81,13% of biological efficiency. The rice straw substrata provides the higher productivity and biological efficiency for all tested strains. The nutricional quality of mushroons varies as the used substratum. P. ostreatoroseus and P. pulmonarius demonstrated an lower fat content and its basidiomata acumulate more minerals when it grows in castor bean seed husks. Finally, it is observed that the most productivity was obtained at the first flow of production for all tested strains.